2015
DOI: 10.4336/2015.pfb.35.83.493
|View full text |Cite
|
Sign up to set email alerts
|

Influência do comprimento de copa na relação hipsométrica de Araucaria angustifolia

Abstract: <p class="Default"><span>Este trabalho teve como objetivo testar a hipótese de que o comprimento de copa afeta a relação hipsométrica. Os dados utilizados são provenientes da medição de diâmetro a 1,30 m do solo (DAP) e respectivas alturas totais e do fuste de 337 indivíduos de <em>Araucaria angustifolia </em>(Bertol.) O. Kuntze de um fragmento de 15,24 ha de Floresta Ombrófila Mista situado na região urbana de Curitiba. Estas árvores foram agrupadas em classes de comprimento de copa. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…The effect of stand density on the height-diameter relationship was evaluated by Silva et al (2016), who found an accuracy reduction of the height estimates of Tectona grandis L. F., for wider spacings; similar results were found by Bartoszeck et al (2004). Concerning the effect of the variables sociological position and crown length, Costa et al (2014) and Machado et al (2015) found height-diameter equations with better statistical performance fitted into sociological position and crown length classes, respectively.…”
Section: Introduction and Objectivesmentioning
confidence: 66%
See 1 more Smart Citation
“…The effect of stand density on the height-diameter relationship was evaluated by Silva et al (2016), who found an accuracy reduction of the height estimates of Tectona grandis L. F., for wider spacings; similar results were found by Bartoszeck et al (2004). Concerning the effect of the variables sociological position and crown length, Costa et al (2014) and Machado et al (2015) found height-diameter equations with better statistical performance fitted into sociological position and crown length classes, respectively.…”
Section: Introduction and Objectivesmentioning
confidence: 66%
“…The height-diameter relationship is susceptible to several factors, such as site quality (Retslaff et al, 2015;Vendruscolo et al, 2015), age (Machado et al, 2011;Paulo et al, 2011;Soares & Tomé, 2002;Téo et al, 2017), stand density (Araújo et al, 2012;Silva et al, 2016;Téo et al, 2017), crown size (Machado et al, 2015), species (Azevedo et al, 2011;Donadoni et al, 2010;Hess et al, 2014;Sanquetta et al, 2013) and the sociological position of the trees (Costa et al, 2014;Leduc & Goelz, 2009;Martins et al, 2016). Retslaff et al (2015) reported that the use of the variables dominant height and site index produced height-diameter equations with more homogeneous and narrow residues distribution.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Machado et al (2015), found improvement in fit and precision of h/d models when separating Araucaria trees in crown length classes. They also found that Araucarias with larger crown lengths tend to be taller and thicker.…”
Section: Discussionmentioning
confidence: 99%
“…A escolha da melhor equação hipsométrica ajustada, para o conjunto dos dados, foi realizada com base nos critérios do erro padrão da estimativa em percentagem (S yx %) e do coeficiente de determinação ajustado em percentagem (R²aj%). Nos casos de equações logaritmizadas, visto que essas equações tendem a subestimar os valores da altura, utilizou-se um fator de conversão, visando corrigir esse erro, por meio da multiplicação das alturas estimadas pelo Fator de Meyer (FM) para recalcular o erro padrão da estimativa, conforme descrito por Machado et al (2015). Já o índice de ajuste de Schulaegel (IA) foi utilizado visando permitir a comparação com o coeficiente de determinação ajustado (R²aj%) das equações de diferentes naturezas (MACHADO et al, 2015).…”
Section: Avaliação E Escolha Dos Modelosunclassified